0.1(x+40)-0.04(x-60)=10

Simple and best practice solution for 0.1(x+40)-0.04(x-60)=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.1(x+40)-0.04(x-60)=10 equation:


0.1(x+40)-0.04(x-60)=10

We simplify the equation to the form, which is simple to understand
0.1(x+40)-0.04(x-60)=10

Reorder the terms in parentheses
+( + 0.1x+4)-0.04*(x-60)=10

Remove unnecessary parentheses
+ 0.1x+4-0.04+*(+x-60+)=+10

Reorder the terms in parentheses
+ 0.1x+4+(-0.04x+2.4)=10

Remove unnecessary parentheses
+ 0.1x+4-0.04x+2.4=+10

We move all terms containing x to the left and all other terms to the right.
+ 0.1x-0.04x=+10-4-2.4

We simplify left and right side of the equation.
+ 0.06x=+3.6

We divide both sides of the equation by 0.06 to get x.
x=60

See similar equations:

| -9-3x=-7 | | -4x-9+8=19 | | 5x^2-95x-20=0 | | 5x+-2=4(2x+6) | | -6(t-2)-(t+5)=11 | | -14+25=x-4 | | 6(x+3)+3=-11(x-1)-5 | | Y-6x=0 | | 9f^3-7f^2-2+9f^3+3f^2+6f= | | 7r^2-343=0 | | 0.0375x+0.075x=675 | | -2m-28=0 | | -3y-7(-1y+4)=-4+4(-8-y) | | 3x+-7=2(3x+1) | | -6+10x=x+12 | | 3x-3=3x-8 | | -3n-2=-23 | | 3(9)-3x=6 | | 8z=17-25 | | 18x^2+25x+3=0 | | 3x-3=-3x-8 | | 7-6w=-5 | | 4x-2(x-3)=-8+5x+5 | | 9(x+2)+2=-2(x-3)-7 | | y^4+6y^2+5=0 | | -48+6x=3x+12 | | X^2+10x+25=16 | | 7x^2-7x-210=0 | | 11x-3=10(x+9)+4 | | 5+ln(-7x+8)=0 | | 3(m+3)=30 | | 8y+3=19 |

Equations solver categories